Premises for post-penal isolation. Considerations based on the case law of common courts and the Supreme Court - Jędras, Franciszek; Grabarczyk, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The discussed Act introduced an institution of post-penal isolation into the Polish legal system. The scientific community widely criticised this regulation at the stage of the legislative process and assessed it as being hasty and ill-conceived. The statue was alleged to be only a response to the social demand arising out of fear of prison release of the extremely dangerous perpetrators who had been serving the sentence of 25 years’ imprisonment. Doubts of the doctrine were focused on the manner of defining the subjective scope of the Act. It was assessed as imprecise and arousing fundamental interpretative doubts which may result in its provisions being referred to the overly wide range of addresses. The analysis of the case-law of common courts and the Supreme Court indicates, however, that the regulation is applied with great caution and the courts use the procedural possibilities resulting from the non-contentious civil procedure to prevent unauthorized interference with human freedom and its status as a legal entity.